2007
DOI: 10.1103/physreva.75.043604
|View full text |Cite
|
Sign up to set email alerts
|

Stability and entanglement in optical-atomic amplification of trapped atoms: The role of atomic collisions

Abstract: Atomic collisions are included in an interacting system of optical fields and trapped atoms allowing field amplification. We study the effects of collisions on the system stability. Also a study of the degree of entanglement between atomic and optical fields is made. We found that, for an atomic field initially in a vacuum state and optical field in a coherent state, the degree of entanglement does not depend on the optical field intensity or phase. We show that in conditions of exponential instability the sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Entanglement has been investigated in many different physical systems, such as photons in optical cavities [3], ultracold atoms interacting with light [4,5], and in solid-state systems [2], where it has been associated with particle-particle correlations [6].…”
Section: Introductionmentioning
confidence: 99%
“…Entanglement has been investigated in many different physical systems, such as photons in optical cavities [3], ultracold atoms interacting with light [4,5], and in solid-state systems [2], where it has been associated with particle-particle correlations [6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, collisions among excited state atoms, as well as, collisions between ground state atoms with excited state ones, are very improbable and can also be neglected. In this regime the excited state can be adiabatically eliminated and the ground state atomic field plus the optical probe evolve coherently under the effective Hamiltonian [17,18,19] is the trap potential. ∆ = ω 2 − ν is the detuning between the atomic transition and the optical pump frequencies, g 1 and g 2 are the atom-light coupling coefficients, and k = k 1 − k 2 .…”
Section: Modelmentioning
confidence: 99%
“…Nonetheless, the interaction of the atomic system with a quantized light probe field can be engineered with the assistance of an additional pump field (See [11] for an excellent review on this topic). This scheme allows, e.g., the simultaneous amplification of atomic and optical fields, as well as control of the atomic field statistical properties [16,17,18]. Previously, with a setup relying on the atomic system-probe field interaction mediated through a classical pump [19], we showed that under continuous photo-counting, the moments of the probe light photon number might carry information about the even moments of the atom number.…”
Section: Introductionmentioning
confidence: 99%
“…Entanglement, which is a theoretical concept from quantum information theory, has attracted attention from nanoscience and nanotechnology since it is considered a fundamental resource for quantum computation 1,2 and quantum-enhanced metrology 3 . Entanglement has also played a central role in bridging quantum information theory to different areas, as condensed-matter, high-energy and cold-atoms physics [4][5][6][7][8][9][10][11][12][13][14][15][16][17] . By investigating entanglement properties one can probe quantum phase transitions [18][19][20][21][22][23] and characterise quantum many-body states, including exotic states of matter as Fulde-Ferrel-Larkin-Ovchnnikov superfluidity (FFLO) [24][25][26][27][28][29][30] , many-body localization 31,32 and topological spin liquids 33 .…”
Section: Introductionmentioning
confidence: 99%